1998
DOI: 10.2307/4003197
|View full text |Cite
|
Sign up to set email alerts
|

Spring Burning: Resulting Avian Abundance and Nesting in Kansas CRP

Abstract: Spring burning is used to control invasion by woody vegetation of rangelands in eastern Kansas and also of Conservation Reserve Program (CRP) fields planted to native grasses. We measured the effects of spring burning of CRP fields on vegetation structure and avian populations in northeastern Kansas during the summers of 1992 through 1995. Several vegetation characteristics differed between burned and unburned CRP fields in May, but few differed in July. Mean avian abundance on burned CRP fields was 5.6 birds … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
27
1

Year Published

1999
1999
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(32 citation statements)
references
References 16 publications
4
27
1
Order By: Relevance
“…Indeed, the estimated difference in blackbird density between unburned and burned fields accounted for 78% of the difference for combined density of all grassland and wetland species. In contrast, some past studies have found no effect (Herkert, 1994) or increases in red-winged blackbirds after burning (Zimmerman, 1992); however, others have found decreases (Robel et al, 1998). Consistent with our results from the year fields were burned (2001), past research suggests that common yellowthroats are negatively impacted by burning of their habitat (Zimmerman, 1992;Herkert, 1994;Madden et al, 1999).…”
Section: Density Species Richness and Conservation Valuesupporting
confidence: 80%
See 3 more Smart Citations
“…Indeed, the estimated difference in blackbird density between unburned and burned fields accounted for 78% of the difference for combined density of all grassland and wetland species. In contrast, some past studies have found no effect (Herkert, 1994) or increases in red-winged blackbirds after burning (Zimmerman, 1992); however, others have found decreases (Robel et al, 1998). Consistent with our results from the year fields were burned (2001), past research suggests that common yellowthroats are negatively impacted by burning of their habitat (Zimmerman, 1992;Herkert, 1994;Madden et al, 1999).…”
Section: Density Species Richness and Conservation Valuesupporting
confidence: 80%
“…In this study, we found decreases in density of grassland and wetland species, and density of two species, common yellowthroats and red-winged blackbirds following burning. Past studies found little effect of burning on density of all species combined (Madden et al, 1999), or decreases in density (Zimmerman, 1992;Robel et al, 1998). Most of the observed decrease in density of all grassland and wetland species combined in our study was driven by changes in red-winged blackbird density, the most abundant species on our study area.…”
Section: Density Species Richness and Conservation Valuesupporting
confidence: 41%
See 2 more Smart Citations
“…Eddleman (1974) observed Upland Sandpipers on heavily grazed/annually burned pasture, moderately grazed/unburned pasture, and ungrazed/burned areas; Upland Sandpipers did not use unburned/ungrazed areas. Robel et al (1998) found that Upland Sandpipers were present only on spring-burned, seedednative CRP fields and not on unburned fields. Bowen (1976) observed that Upland Sandpiper abundance did not differ between burned and unburned pastures in Kansas.…”
Section: Brown-headed Cowbird Brood Parasitismmentioning
confidence: 91%